Analisis Strategi Marketing Mix dalam Perspektif Ekonomi Syariah UMKM Hasma Jaya Lestari - Naili Jazilinni’am (Nomicpedia: Journal of Economics and Business Innovation, 2022)
Integrated marketing activities are called the marketing mix. Each element in the marketing mix such as promotion, price, product, and place requires an individual strategy. However, there are still many business activities that are implemented in the community that are not in accordance with the sharia provisions. Hasma Jaya Lestari is one of them, an UMKM (micro small and medium enterprises) that produces soy milk. It is located in Kranji Village, Paciran, Lamongan. UMKM Hasma Jaya Lestari has started its business on April 30, 2003, 18 years ago and is the first UMKM to produce soy milk in Paciran. Hasma Jaya Lestari UMKM was founded by Mr. Hasan Nawawi and Mrs. Muhimmah where has 8 employees. Analyzing the marketing mix strategy in the perspective of Islamic economics in UMKM (micro small and medium enterprises) Hasma Jaya Lestari is the purpose of this study. This study uses descriptive-qualitative study as the approach. Researcher uses primary and secondary data sources. Data sources used in this study are primary and secondary; which direct interviews with UMKM owner Hasma Jaya Lestari were conducted to fulfill the primary data. While the secondary data sources are reference from journals and literature on the marketing mix of Islamic economic perspective. Based on the results of the research, it can be concluded that the application of a marketing mix strategy in a sharia economic perspective in Hasma Jaya Lestari UMKM (micro small and medium enterprises) located in Kranji has implemented a 4P marketing strategy based on a sharia economic perspective. For further research, the suggestion of this study would be better if the research was conducted by investigating for the influence of the marketing mix strategy in an Islamic economic perspective on the level of sales turnover.